1993
DOI: 10.1159/000196206
|View full text |Cite
|
Sign up to set email alerts
|

<i>Mycoplasma pneumoniae</i> Infection in Hong Kong – Clinical and Epidemiological Features during an Epidemic

Abstract: An epidemic of infection due to Mycoplasma pneumoniae occurred in Hong Kong in 1986-1988. One hundred and seventy-nine cases were identified at the Prince of Wales Hospital over this period. Clinically significant infection predominantly affected children under 12 years, with 32% of all infections occurring in children aged between 6 and 11 years, and 39% in children between 1 and 5 years. Ninety-seven percent of childhood infections were respiratory in nature, the other 4 presentations were neuropsychiatric. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
(10 reference statements)
0
7
1
Order By: Relevance
“…With respect to MP, our average rate was lower than the 15-20% usually reported [20], but higher rates have sometimes been found [16,19] particularly in investigations of local epidemics. However, between 1970 and 1972, 7% of the LRTI cases studied in the UK were positive for MP [20], a proportion similar to the one found in our subset of patients with radiologically confirmed CAP. Our network was not representative of all French practitioners, since its members were recruited on a voluntary basis from an existing network, and not at random.…”
Section: Discussioncontrasting
confidence: 71%
“…With respect to MP, our average rate was lower than the 15-20% usually reported [20], but higher rates have sometimes been found [16,19] particularly in investigations of local epidemics. However, between 1970 and 1972, 7% of the LRTI cases studied in the UK were positive for MP [20], a proportion similar to the one found in our subset of patients with radiologically confirmed CAP. Our network was not representative of all French practitioners, since its members were recruited on a voluntary basis from an existing network, and not at random.…”
Section: Discussioncontrasting
confidence: 71%
“…[12] reported a higher frequency of this pattern (38%) in paediatric patients in Taiwan, whereas Hosker et al . [13] reported that 95% of paediatric patients presented with this pattern in Hong Kong and Defilippi et al . [14] showed that consolidation was the commonest finding in children with infection due to M. pneumoniae in Genoa.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of community spread, transmission of M. pneumoniae within schools was relatively low compared with the spread of this bacterium within families and infections among neighborhood playmates in the United States (6). Although outbreaks of M. pneumoniae in China have been reported (8,11,14), this is the first report of a point source outbreak caused by a rare macrolide-resistant strain of M. pneumoniae in China, and this outbreak attracted great attention from local government and public health departments.…”
Section: Discussionmentioning
confidence: 99%